Change in the woody floristic composition, diversity and structure from protected to unprotected savannahs in Pendjari Biosphere Reserve (Benin, West Africa). - HOUEHANOU, Thierry Dèhouégnon; GLELE KAKAI, ROMIN LUCAS; ASSOGBADJO, ACHILLE EPHREM; KINDOMIHOU, M. VALENTIN; HOUINATO, MARCEL ROMUALD BENJAMIN; RÜDIGER, Wittig; SINSIN, AUGUSTIN BRICE (My University, 2012)
Savannahs are widespread vegetation type in Sudanian zone of Africa. As protected areas are often assumed to be the best way to conserve biodiversity, we assessed the effectiveness of the Pendjari Biosphere Reserve in Benin, for maintaining savannah woody species composition, diversity and structure. Square plots of 900 m2 were randomly established in protected and surrounding unprotected savannahs, and all woody species (dbh 1 cm) were recorded and identified. Species composition, Importance Value Index, densities, basal area and diversity indexes were assessed in relation to conservation status. The results showed that DCA based on presence/absence species data did not separate clearly protected savannahs from unprotected ones. However, some species were prominent in unprotected savannahs while others showed the same scheme in protected ones. Diversity indexes indicated a good distribution of species in the two savannah types. The woody density showed a higher value in protected than unprotected savannah at shrub layer level. The basal area was significantly higher in the protected savannah than unprotected one at the two woody layer levels. It can be concluded that biodiversity conservation in surrounding unprotected areas should be of great importance to increase biodiversity conservation by protected area whether specific actions were implemented.
Keywords: conservation; diversity; savannah; structure; woody species